ChemInform Abstract: Highly Efficient Transition Metal Nanoparticle Catalysts in Aqueous Solutions. Issue 27 (16th June 2016) - Wang, Changlong; Ciganda, Roberto; Salmon, Lionel; Gregurec, Danijela; Irigoyen, Joseba; Moya, Sergio; Ruiz, Jaime; Astruc, Didier
Abstract: A tris(triazolyl)‐polyethylene glycol amphiphilic ligand is designed and successfully used as highly efficient catalyst in combination with various transition metal nanoparticles in click reactions, Suzuki—Miyaura couplings, as well as transfer hydrogenation reactions.